Effect of project-based learning on development of students' creative thinking. Issue 3 (July 2022) - Chen, Shih-Yeh; Lai, Chin-Feng; Lai, Ying-Hsun; Su, Yu-Sheng
In this paper, the study aims to inquire into the impact of integrating creative thinking teaching through project-based learning in the engineering course. In the beginning, the quasi-experiment is implemented in the engineering course. The lecture-based teaching strategy is applied to the control group, while the experimental group applied the project-based learning strategy. All of the students are asked to propose their draft scheme of final project in the middle term, and then implement one system prototype as the final project in the end of semester. The draft scheme and prototype are reviewed by experts for measuring whether creativity has increased or not. Finally, a satisfaction questionnaire is delivered to evaluate the students' opinions about the experimental classroom. The results show that the project-based learning approach is able to promote the creative thinking of students, especially with regard to fluency and flexibility. Moreover, the students in their interview thought suitable creativity thinking tools are an approach that can promote their creativity significantly. Hence, the various creative thinking tools must be provided for students in order to take advantage of developing creativity thinking habits.